PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG MASUK DALAM INDEX LQ-45 PERIODE 2018-2022 - Aqiela Faidah Haya Samsudin; M. Kausar Maulana (Jurnal Ekonomi dan Industri, 2023)
This study aims to analyze the effect of liquidity and profitability on stock prices included in the LQ-45 index for the 2018-2022 period. This study uses a quantitative method, namely by using secondary data. Data obtained from the company's financial report website for 2018-2022. The results of the partial test (t test) show that liquidity (current ratio) has a negative and insignificant effect on stock prices while profitability (earning per share) has a positive and significant effect on stocks. Based on the results of the simultaneous test (F) shows that liquidity (current ratio) and profitability (earning per share) simultaneously have a significant effect on stock prices.